(Sb2O3/Sb2O5)-doped SnO2–Co3O4–Cr2O3 varistors: The Sb2O4 in-situ formation and its influence over the electrical and microstructural properties. Issue 1 (1st January 2021) - Miranda-López, Martin I.; Sánchez Rico, V.; Hernández, M.B.; Falcon-Franco, L.; García-Villarreal, S.; Zambrano-Robledo, P.; Esneider-Alcalá, Miguel; García-Ortiz, L.; Aguilar-Martínez, J.A.
Abstract: The present study aimed to systematically study the transitions and consequential effects of antimony oxide (Sb2 O3 or Sb2 O5 ) additions over the properties of a SnO2 -based varistor system. High energy ball-milling and conventional sintering were used to obtain the samples with the following molar composition: (98.95-X)% SnO2 - 1% Co3 O4 - 0.05% Cr2 O3 - X% Sb2 O3 /Sb2 O5 where X = 0, 0.05, 0.1, 0.2 and 0.4 mol%. The thermal analysis suggested the in-situ formation of Sb2 O4 at ~450 °C from Sb2 O3 or Sb2 O5 during the sintering of mixed oxides. SEM, XRD, and electrical analysis revealed similar results by using Sb2 O3 or Sb2 O5 ; the addition of 0.05 mol% antimony oxide provides the foremost properties. The transition equations from Sb2 O3 or Sb2 O5 to Sb2 O4 demonstrate equivalency in the amount of Sb2 O4 formed. That fact, besides the results obtained, were used to discuss a reasonable route for Sb 3+ and Sb 5+ incorporation within the SnO2 lattice.